2006
DOI: 10.1111/j.1365-2125.2006.02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response in direct comparisons of different doses of aspirin, ibuprofen and paracetamol (acetaminophen) in analgesic studies

Abstract: AimsEstablishing the dose-response relationship for clinically useful doses of aspirin, ibuprofen and paracetamol has been difficult. Indirect comparison from meta-analysis is compromised by too little information at some doses. MethodsA systematic review of randomized, double-blind trials in acute pain comparing different doses of aspirin, ibuprofen and paracetamol was therefore under taken. ResultsFifty trials were found. Numerical superiority of higher over lower dose was found by the original authors in 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 51 publications
1
30
0
1
Order By: Relevance
“…This study found that for the 200 mg/30 mg combination starting treatment with two tablets is more efficacious than with a single tablet, irrespective of symptom score or of analytical approach being applied. This is in line with findings from previous studies comparing the efficacy of 50‐400 mg ibuprofen25 or in meta‐analyses of ibuprofen studies in analgesic indications, demonstrating an increased efficacy with higher doses in the 200‐800 mg dose range 26. It is also in line with dose‐ranging studies with 15‐180 mg pseudoephedrine effects on nasal airway resistance 19.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that for the 200 mg/30 mg combination starting treatment with two tablets is more efficacious than with a single tablet, irrespective of symptom score or of analytical approach being applied. This is in line with findings from previous studies comparing the efficacy of 50‐400 mg ibuprofen25 or in meta‐analyses of ibuprofen studies in analgesic indications, demonstrating an increased efficacy with higher doses in the 200‐800 mg dose range 26. It is also in line with dose‐ranging studies with 15‐180 mg pseudoephedrine effects on nasal airway resistance 19.…”
Section: Discussionsupporting
confidence: 90%
“…The first, second and third groups were given standard therapeutic dose equivalent of ibuprofen [12]: 20 mgkg -1 daily (in two divided doses) for 7, 14 and 28 days, respectively. The fourth, fifth and sixth groups were given 40 mgkg -1 of ibuprofen daily (in two divided doses) for 7, 14 and 28 days, respectively.…”
Section: Experimental Designmentioning
confidence: 99%
“…93,94 Using a dose-response study design, McQuay and Moore demonstrated that 1 g of acetaminophen produced greater benefits than a dose of 600-650 mg, with a number needed to treat (NNT) of 9. 95 When acetaminophen was combined with codeine, the NNT decreased to 2.2. 95 One systematic review that compared acetaminophen versus NSAIDS revealed mixed results; 96 the authors concluded that the treatment of postoperative pain was superior when the agents were combined than when either single agent was administered alone.…”
Section: Acetaminophenmentioning
confidence: 99%
“…95 When acetaminophen was combined with codeine, the NNT decreased to 2.2. 95 One systematic review that compared acetaminophen versus NSAIDS revealed mixed results; 96 the authors concluded that the treatment of postoperative pain was superior when the agents were combined than when either single agent was administered alone. Acetaminophen's efficacy in treating mild to moderate pain, combined with its relatively benign side-effect profile (no gastric irritation or platelet aggregation effects), explains why it continues to be widely used as part of postoperative multi-modal pain regimens.…”
Section: Acetaminophenmentioning
confidence: 99%